PENGARUH PERAN PERBANKAN DAN PEMERINTAH DAERAH DALAM MENGEMBANGKAN EKONOMI KREATIF DI KABUPATEN PAMEKASA - TRI ADINDA NINGSIH, YULIA; Susandini, Aprilina (JURNAL EKBIS, 2024)
The aim of this research is to determine the influence of the role of banking and local government in developing the creative economy in Pamekasan Regency. The population in this research are creative economy actors in Pamekasan district. The sample from this research was 50 creative economy MSMEs in Pamekasan Regency. The sample technique taken was a purposive sampling technique. The research method used is a quantitative method. Data analysis techniques use validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. From this research, the role of banking does not have a significant effect, because the t test results show 0.318 > 0.05. Meanwhile, local government has a significant influence because the value is 0.000 < 0.05. Simultaneously the influence of the role of banking and local government has a significant influence because the resulting value is 0.000b